Metodologia para avaliação de transformadores de potência através de Health Index e modelo de envelhecimento - Oliveira, Micael Márcio (2021)
The power transformers conditions assessment are essential for the management of this equipment, allowing the identification of maintenance interventions or replacements demands, as well as assisting in financial planning. In this context, this work presents a methodology for power transformers evaluation, with the elaboration of a Health Index and aging model, combined intro the equipment apparent age method. The proposed aging estimation method uses hotspot temperature measurements, together with the moisture in the conductors insulating paper, to determine the remaining service life of the transformers. In the Health Index model, the parameters related to the power transformers components conditions are evaluated using fuzzy logic, being the configurations based on current standards, previous strategies and the experience of specialists. These two aspects, aging and Health Index, form the apparent age of transformers, resulting in a robust tool for asset management. This methodology was then applied to a case study, using the monitoring data of the five power transformers located at the Santo Antônio hydroelectric plant, with the analysis of the aging and condition of this equipment. As results, the methodology indicated the transformers to be prioritized in maintenance interventions, the aging rate and the remaining useful life of the equipment. Further, the apparent age made possible an overview of the global state of the transformers, appointing the units with the most critical state. In addition, a framework of actions was prepared, based on the application of the methodology, providing the plant’s management and maintenance team with support in decision making regarding power transformers.